Periodontal Involvement in Leukocyte Adhesion Deficiency: Review of the Literature and a Case Report - Seyfi, Nasim; Sabzeghabaie, Mehrnoosh; Dehghankhalili, Sara (Journal of Dental School, 2019)
Objective: Leukocyte adhesion deficiency (LAD) is a rare, autosomal recessive inherited disorder; LAD-I which is the most common type, occurs due to mutations in the CD18 gene. This mutation down-regulates the expression of ß2 integrin leukocyte cell surface molecules, which are necessary for the adhesion of leukocytes to endothelial cells, transendothelial migration, and chemotaxis. The major symptoms are recurrent severe bacterial infections without pus formation, recurrent or progressive necrotizing soft tissue infections, marked leukocytosis and severe progressive periodontitis accompanied by alveolar bone loss, periodontal pockets, and partial or total early loss of primary and permanent teeth. Cases: Herein, we report a case of moderate LAD-I in a nine year-old boy with severe alveolar bone loss and aggressive periodontitis. For several years, approximately every month, the patient was followed up to evaluate the status of primary and permanent dentition. During these visits, scaling and root planing were performed and severely mobile teeth were extracted. The patient is now under regular follow up. Conclusion: This case confirms the need for interactions between the medical groups to identify and manage medically compromised children with rare diseases. It is important to include LAD in the differential diagnoses of children presenting with periodontal disease. Early correct diagnosis of LAD has various benefits for patients.